Broad-Spectrum Antimicrobial, Antioxidant, and Anticancer Studies of Leaf Extract of Simarouba glauca DC In Vitro - Shanmuga Priya Ramasamy; Anitha Rajendran; Muthukrishnan Pallikondaperumal; Priya Sundararajan; Fohad Mabood Husain; Altaf Khan; Mohammed Jamal Hakeem; Abdullah A. Alyousef; Thamer Albalawi; Pravej Alam; Hazim M. Ali; Abdulaziz Alqasim (MDPI AG, 2022)
The current study aimed to screen the preliminary phytochemicals in the leaf extract of the medicinal plant Simarouba glauca and to analyze its potential antimicrobial, antioxidant and anticancer properties. The phytochemical profile of the methanol extract was analyzed, and bioactive compounds were identified using chromatography, FTIR and GCMS. Antimicrobial activity and Minimum Inhibitory Concentration (MIC) were determined against 14 bacterial and 6 fungal strains. Moreover, the synergistic effect of a plant extract with commercially available antibiotics was also evaluated using the checkerboard method. The ethanolic and methanolic extracts showed exclusive activity against S. aureus and profound activity against E. coli and S. marcescens. Upon comparing breakpoints, methanolic extract demonstrated higher antimicrobial activity with a MIC value of 3.2 mg/mL against the test pathogens. Furthermore, the extracts demonstrated potential antioxidant activity; methanol extract had higher antioxidant potential compared to the ethanol extract. The major proactive bioactive compound with maximum antioxidant capacity was observed to be terpenoids. The methanol extract of S. glauca showed significant cytotoxicity against the MCF-7 breast cancer cell line with an IC50 value of 16.12 µg/mL. The overall results of our work provide significant evidence for the usage of methanolic extract of S. glauca as an efficient ethnomedicinal agent and a potential candidate for relieving many human ailments.